2019
DOI: 10.11604/pamj.2019.34.2.20016
|View full text |Cite
|
Sign up to set email alerts
|

Profil évolutif de l'insuffisance rénale aiguë chez les personnes vivant avec le VIH à Abidjan, Côte d'Ivoire du 1er janvier 2014 au 31 décembre 2017

Abstract: En Côte d'Ivoire, la prévalence de l'infection au virus de l'immunodéficience humaine (VIH) est élevée. Tous les organes peuvent être atteints, en particulier le rein. Certaines études en Côte d'Ivoire ont retrouvé les infections opportunistes comme facteur de mauvais pronostic de l'insuffisance rénale aiguë (IRA). L'objectif de cette étude était de rechercher les éventuels autres facteurs associés à l'évolution de l'IRA chez les personnes infectées par le VIH. Une étude rétrospective, analytique, menée au Cen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…AKI occurs most often in advanced disease and may also be secondary to the use of nephrotoxic drugs common in these patients or to shock. A prospective study of 317 HIV-infected patients in Abidjan (in Ivory Coast) found AKI in 76 patients (24%) [ 75 ]. In a cohort of 101 HIV-infected South Africans with AKI, the most common cause of AKI was sepsis (60%), followed by volume depletion and haemodynamic instability [ 76 ].…”
Section: Factors Associated With Aki In Sub-saharan Africamentioning
confidence: 99%
“…AKI occurs most often in advanced disease and may also be secondary to the use of nephrotoxic drugs common in these patients or to shock. A prospective study of 317 HIV-infected patients in Abidjan (in Ivory Coast) found AKI in 76 patients (24%) [ 75 ]. In a cohort of 101 HIV-infected South Africans with AKI, the most common cause of AKI was sepsis (60%), followed by volume depletion and haemodynamic instability [ 76 ].…”
Section: Factors Associated With Aki In Sub-saharan Africamentioning
confidence: 99%